Pemodelan Spasial Transportasi Karbon Biru di Ekosistem Bakau Menggunakan Data Multispektral dan Hidrodinamika - Fendra Dwi Ramadhan; Luthfiya Ratna Sari; Siti Noor Chayati; Farouki Dinda Rasarrandi; Arif Rahman (Indonesian Journal of Applied Geography, 2026)
Mangrove ecosystems play a vital role in storing blue carbon, which helps combat climate change. This research aims to simulate blue carbon transport by integrating multispectral data with hydrodynamic models in the Kampung Tua area of Tanjung Piayu, Batam City. Field data was collected between April 15 and April 30, 2025. The methods included the examination of Sentinel-2A and Landsat 8 satellite images to derive key indicators, including the Normalized Difference Vegetation Index (NDVI), Total Suspended Solids (TSS), Chlorophyll-a levels, Land Surface Temperature (LST), and Sea Surface Temperature (SST). Hydrodynamic simulations were conducted using the MIKE 21 Flow Model FM module to replicate ocean current behaviors. Multiple linear regression revealed that these six variables had a substantial impact on blue carbon distribution (F = 593.045; p < 0.001), achieving an R² value of 0.78. The prevailing current direction was semi-diurnal, moving from east to southwest, which promotes the movement of organic matter into the mangrove zones along the northern shoreline. Combining these techniques successfully enabled spatial mapping of blue carbon potential, laying the groundwork for effective and sustainable coastal ecosystem management strategies.